Metode Role-Playing Dan Penggunaan Platform Youtube Untuk Meningkatkan Speaking Skill Siswa (Pengabdian Masyarakat Di Madrasah Aliyah Mu’min Cendekia) - Enny Diah Astuti; Retno Setya Budiasningrum; Jajang Setiawan; Ali Satri Efendi; Rahmi Rosita; Dyan Yuliana (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The capacity to converse is a person's communication talent. In the classroom, English acts as a tool for communication to gather information, and in real-world situations, it is used to build relationships and communicate information. The ineffective teaching strategies utilized by teachers during the learning process contribute to the poor results of English learning. Role-playing is the technique employed in this activity, which is one of the language learning techniques in the application of communication that can forge relationships in social interactions and learning to boost student accomplishment orally in the use of language that includes meaning. There are three steps to this activity's execution. Students are provided a theoretical explanation by the teacher in the initial step. Role-playing techniques are used in English learning and are thought to be very successful. In the process, a number of noteworthy benefits of the role-playing approach of this learning were discovered relative to its drawbacks. Students find role-playing to be an acceptable and enjoyable technique of learning. The participants gained enthusiasm, motivation, and self-assurance in their ability to communicate in English.